Penggunaan Simple Additive Weighting Dalam Pengembangan Sistem Penunjang Keputusan Penentuan Bonus Karyawan - Meta Amalya Dewi (ULTIMA InfoSys, 2018)
Employees are the important aspect to determine company progress. PT. Adiperkasa Anugrah Pratama is a company which engaged in manufacturing by giving bonuses to employees as appreciation action, in determining the employees bonuses they have no precise calculation and potential subjectivity to describe employees dissatisfaction. This research is conducted by using simple additive weighting (SAW) method. This method can find the best alternative to determine the amount of employees bonus by finding job period, job position, departmental function and performance value. This method can determine the solution and the optimal alternative. The application designed by Unified Modeing Language (UML) that implemented in PHP programming language with sublime text 3 and MySQL database type. The result of this study is a supportive system that can assist the management in determining the bonus amount of the employees. Index Terms—employee, position, bonuses, performance.